2022
DOI: 10.1021/jacs.1c10248
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Platinum–Copper Nanocrystal Alloy Catalysts Surpass Platinum in Low-Temperature Propene Combustion

Abstract: Low-temperature removal of noxious environmental emissions plays a critical role in minimizing the harmful effects of hydrocarbon fuels. Emission-control catalysts typically consist of large quantities of rare, noble metals (e.g., platinum and palladium), which are expensive and environmentally damaging metals to extract. Alloying with cheaper base metals offers the potential to boost catalytic activity while optimizing the use of noble metals. In this work, we show that Pt x Cu 100−x catalysts prepared from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 56 publications
(80 reference statements)
1
30
0
Order By: Relevance
“…The alloyed Cu-Rh phase obtained after annealing at 800 °C had higher activity for CO oxidation compared to its initial core-shell structure. The effect of alloying Cu and a noble metal on catalytic properties has been reported in previous work. , Complex synergetic effects can potentially explain the increased activity of alloyed Cu-Rh.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alloyed Cu-Rh phase obtained after annealing at 800 °C had higher activity for CO oxidation compared to its initial core-shell structure. The effect of alloying Cu and a noble metal on catalytic properties has been reported in previous work. , Complex synergetic effects can potentially explain the increased activity of alloyed Cu-Rh.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The effect of alloying Cu and a noble metal on catalytic properties has been reported in previous work. 54,55 Complex synergetic effects can potentially explain the increased activity of alloyed Cu-Rh. The results for the three core-shell particles confirm the presence of exposed precious metals, with no Cu layer covering the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the present authors have recently demonstrated the promise of this second approach for propene combustion by alloying Pt with the cheaper base metal Cu. 74 In this study, we show that, while monometallic Cu adsorbs O* more strongly than monometallic Pt (adsorption on Cu is stronger by 0.4 eV), adding moderate amounts of Cu (<50 at. %) into Pt actually slightly weakens the oxygen binding strength on the surface by 0.1 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 57%
“…32 This is also consistent with previous publications as Cu is not considered an efficient catalyst for CO oxidation. 41,42,43 .…”
Section: Resultsmentioning
confidence: 99%